Strategies of University Training Bachelors of Translation in the Ukrainian Danubian Region : Array - Soroka, Tetiana (Journal of Danubian Studies and Research, 2021)
The purpose of the article is to identify the practical and theoretical components in the preparation of training programs and courses on the theory and practice of translation, the practice of foreign languages, linguo- cultural studies and disciplines of specialization. When creating practical courses, one should focus on the making the so-called "through programs", built not only on step-by-step training in language skills, but also on mastering the language culture and traditions. These should be multi-purpose courses focused on achieving the following goals: awareness of the existence of linguistic "pictures" of the world, in particular, of English-speaking countries; understanding of the socio-cultural aspect of learning English, which helps to develop a loyal attitude to the English-speaking culture; understanding the hidden content of the English language as a way of international communication; ability to see differences between native and other cultures (traditions, behavior, etc.) and to perceive them positively; mastering a basic knowledge of socio-cultural values and stereotypes; using socio-cultural knowledge in the process of communication, possession of a sufficient amount of vocabulary on the proposed topic; listening to audio and video materials in order to identify basic information and factual details; preparation for the role of a professional cultural mediator between one's own culture and the culture of the country of the language being studied, as well as effective solutions to problems of intercultural misunderstanding and conflicts.